COVID-19 from the perspective of otorhinolaryngology: An analysis of bibliometrics - Wang, Ji; Liang, Sai; Yu, Ming; Gong, Zhengpeng (Frontiers in Public Health, 2022)
Background Since it began in December 2019, the coronavirus disease 2019 (COVID-19) outbreak has not been completely contained. COVID-19 has attracted the interest of nations throughout the globe. The global coronavirus outbreak has had an especially devastating effect on otolaryngology. The virus is commonly associated with otorhinolaryngological symptoms. COVID-19 research is becoming more common in otorhinolaryngology. Although various studies on covid-19-related Otorhinolaryngology manifestations have been published, there has been no bibliometric analysis of these articles concentrating on COVID-19-related Otorhinolaryngology research. Methods Original publications on Otolaryngological symptoms on COVID-19 were extracted from the Social Sciences Citation Index (SSCI) and the Science Citation Index-Expanded (SCI-E) databases in Clarivate Analytics' Web of Science Core Collection (WoSCC) between January 2020 and May 2022. CiteSpace and VOSviewer were utilized to detect and assess the research focus and trends in this field by extracting the country/region, institution, author, journal, references, and keywords related to this topic. Results A total of 631 journals from 97 countries were included in the total of 1,528 articles. Most of the articles on this topic were published in the United States, which had the most citations and the highest H-index. Huazhong University of Science and Technology is the institution with the largest number of articles in the research of COVID-19-related Otorhinolaryngology diseases. Claire Hopkins was the most prolific author belonging to Guy's and St. Thomas' NHS Foundation Trust. Huang CL from Jin Yin-tan Hospital received the most citations among all authors. The most cited article was Clinical features of patients infected with 2019 novel coronavirus in Wuhan, China, which was created by Huang CL. Most of the studies relating to COVID-19 and Otorhinolaryngology diseases were published in the European Archives of Oto-Rhino-Laryngology. Conclusion COVID-related research in the field of otorhinolaryngology has been studied in terms of descriptive quantitative metrics, which show that academics from around the world are working together to combat this pandemic.